Os movimentos da professoralidade e as implicações das políticas municipais de formação continuada - Pereira, Débora Pinheiro (2023)
This research is linked to the Master's in Education course at the Federal University of Santa Maria (UFSM) and aims to understand the implications of the Municipal Literacy and Literacy Program (PROMLA), in the fabric of the teaching profession of teachers who work in the Early Years of Elementary Education of the Municipal Education Network of Santa Maria/RS. The specific objectives were to recognize the developments of PROMLA; identify the professional profile of teachers who participate in PROMLA and learn how teachers develop and configure their training activities based on participation in PROMLA. The program consists of a proposal for continued training for teachers in the Initial Years of the Municipal Education Network of Santa Maria/RS. The theoretical framework of the investigation includes the studies of Bolzan (2016), Bolzan and Powaczuk (2018, 2019), Gatti (2021), Heller (2008), Huberman (1992), Imbernón (2011, 2012), Isaia and Bolzan (2005, 2006), Marcelo Garcia (1999), Pineau (1988), Nóvoa (2009, 2022), Powaczuk (2008, 2012, 2021), Tardif (2002), Vaillant and Marcelo (2012) and Vieira (2007). The methodological approach is qualitative, of the case study type, based on documentary analysis and questionnaire and narrative interviews, with coordinating teachers participating in PROMLA and with the coordinating teachers of SMEd's Initial Years. The process of interpreting the findings focused on a large category called Texture of Professorship, which presents as categorical dimensions: PROMLA, the Professional Profile of teachers participating in PROMLA and the highlighted training experiences and, finally, the Elaborations and teaching constructions about training activities based on participation in PROMLA. In this way, we identified that PROMLA focuses on literacy from the perspective of literacy and in spaces for continued training, which has been reorganizing since 2019, due to the demands and challenges that emerge in the school context. These dynamics set in motion the processes of decentralization of training ongoing in the network, which include Training in Context and the participation of pedagogical coordinators and teachers in its implementation. We recognize as transversal elements to the fabric of teaching the processes of self, hetero, inter and eco-training, as well as the conditions of time and space to enable the professional development of teachers and trigger movements of individuation, based on the leaps of everyday life driven by collaborative networks established. Thus, we highlight that formative experiences influence the construction and reconstruction of meanings and meanings produced in the fabric of teaching.